PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VA SD NEGERI 011 BANJAR XII KECAMATAN TANAH PUTIH - Daud, Damanhuri; ', Jasrida; ', Munjiatun (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The background of this research is the learning outcomes of IPA is low, with an average grade 54.38. Of the 26 students of class VA SD Negeri 011 Banjar XII Kecamatan Tanah Putih, students who completed as many as six peoples and who did not complete while as many as 10 peoples. This research is a classroom action research (PTK) is done to improve science student’s learning outcomes at Class VA SD Negeri 011 Banjar XII Kecamatan Tanah Putih by applying a type of cooperative learning model Numbered Heads Together (NHT). Instrument collecting data in this study is the teacher’s activities sheet , student’s activities sheet and achievement test. This study presents the results of learning derived from the value of the first semester before the action with an average of 54.38 and after the action increased in UH I in Cycle I to 72.8. In the UH II Cycle II increased to 75.3. The activities of teachers in the learning process the first cycle the first meeting is 62.50% and at the second meeting increased to 75.00%. At the first meeting of the second cycle of teacher’s activities increased to 84.37% and in the second meeting of the second cycle increased to 90.62%. Analysis of student activities at the first meeting of the cycle I is 56.25% and increased in the second meeting of the cycle I to 65.62%. At the first meeting of the second cycle of student’s activities is 78.12% and the second meeting of the second cycle increased to 84.37%. Results of research at class VA SD Negeri 011 Banjar XII Kecamatan Tanah Putih prove that the implementation of cooperative learning model Numbered Heads Together (NHT)Type can improve learning outcomes of IPA Class VA SD Negeri 011 Banjar XII Kecamatan Tanah Putih.Keywords: Cooperative Learning Model Numbered Head Together (NHT) Type, IPA Learning Outcomes.